Labor and Democracy in Nepal: A Look into the Future - Dahal, Dev Raj (Socio-Economic Development Panorama, 2009)
The political change in Nepal has expanded the space for leftout sector of society including workers. The subsequent Constituent Assembly (CA) election has provided the Nepalese workers institutional means to participate in the legislative power of the state, and moved politics from its traditional domain of adjudicating competing claims for positions to structural transformation of public sphere. The success of workers largely depends on how they strengthen their unions; organize inter-institutional movement building and effect collective action in constitution-making, policy mediation and distributional benefits. There is an additional need for the workers to take in the future: work for the sound industrial relations as a mechanism for poverty alleviation, employment generation and peace building, so as to lift the citizens in general and workers in particular out of social, economic and political crises. A vibrant trade union movement in the country serves the democratic nation-building process by holding political leaders accountable, by calling attention to the issues of public concern, by educating workers, and by connecting workers with each other to cope with the challenges of regional and global integration processes. Key words: Labour; democracy; union; workers right; movement building; CA; social transformation Socio Economic Development Panorama; Vol. 1; No. 4, 2009; January-June